Democratic Constitutions, Electoral Commissions and Legitimacy – The Example of Australia. (7th December 2021) - Kildea, Paul; Murray, Sarah
Abstract: This article explores the structure, management and institutional design of commissions in Australia and unpacks how these institutions operate within the Australian political landscape. Part 1 looks at the structure of Australian electoral commissions and how they maintain structural independence. Part 2 seeks to better understand Australian electoral institutions, through an examination of how they have manoeuvred administrative and political challenges and emergencies when they have arisen. Finally, Part 3 employs a neo-institutionalist lens to focus on the internal and external dynamics that assist or hinder the operation of commissions in Australia and how legitimacy and institutional trust can be created, maintained and harmed by electoral agencies in the Australian context.